PENGARUH PENGGUNAAN PETA PIKIRAN (MIND MAPPING) TERHADAP HASIL BELAJAR KKPI DI SMK NEGERI 1 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Nelva Yanti; Zulhendra Zulhendra; Hanesman Zulhendra (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The problem in this study was obtained student learning outcomes is low, this is one of the educational problems that occur for students, and can be used as an indicator of the quality of education is still low. This study aims to determine the effect of the use of mind mapping on learning outcomes in subjects KKPI SMK 1 Valley Crossing West Pasaman. This study is an experimental study, this study population is X1 grade students of SMK N 1 Valley Melintang that follow KKPI subjects. The sampling technique sampling porposive done. Data collected from the test results in the form of learning as much as 29 objective questions about the item. Data were analyzed using Microsoft Excel to test homogeneity, normality, and hypothesis testing. From the test results of the study obtained an average value of students who use mind mapping is 80.04 while the control group of students who use conventional teaching lower at 70.7 . The results of the hypothesis by using Microsoft Excel found that tcount 5.97 > ttable 1.670 , so the alternative hypothesis ( H1 ) is accepted or rejected the null hypothesis ( H0 ). This means that the average significant learning outcomes experimental class larger than average learning outcomes control class Kata Kunci : mind mapping, using, learning outcomes